HIV and HCV screening by non-infectious diseases physicians: can we improve testing and hidden infection rates? - García-Ruiz de Morales, Alejandro G.; Martínez-Sanz, Javier; Vivancos-Gallego, María J.; Sánchez-Conde, Matilde; Vélez-Díaz-Pallarés, Manuel; Romero-Hernández, Beatriz; Vázquez, María Dolores González; de Luque, Carmen María Cano; González-Sarria, Ander; Galán, Juan Carlos; Rodríguez, Francisco Gea; Moreno, Santiago; et al. (Frontiers in Public Health, 2023)
Missed opportunities for Human Immunodeficiency Virus (HIV) and Hepatitis C Virus (HCV) testing remain high. We aimed to ascertain the knowledge of screening guidelines and attitudes of non-infectious diseases (ID) hospital physicians and to assess the impact of a 1-hour session on screening rates and diagnoses. Interventional study consisting of a 1-hour training session on HIV and HCV epidemiology and testing guidelines to non-ID physicians. Pre- and post-session questionnaires compared the knowledge of the guidelines and attitudes towards screening before and after the session. Rates of screening and diagnoses were compared in three 6 months periods: before, immediately after, and 24 months +/- 4 after the session. 345 physicians from 31 departments attended the sessions. Pre-session, 19.9% (28% medical, 8% surgical) and 17.9% (30% medical, 2.7% surgical) were aware of HIV and HCV testing guidelines, respectively. The willingness to routinely test increased from 5.6% to 22%, while not ordering tests decreased from 34.1% to 2.4%. HIV screening rates significantly increased by 20% after the session (7.7 vs. 9.3 tests per 103 patients;p<0.001), and the effect continued until the long-term period. HIV diagnoses rate increased globally (3.6 vs. 5.2 HIV diagnoses per 105 patients;p=0.157), mainly due to medical services (4.7 vs. 7.7 per 105 patients; p=0.082). HCV screening rate increased significantly immediately and in the long-term only in medical services (15.7% and 13.6%). New active HCV infection rates increased immediately and declined steeply afterwards. A short session to non-ID physicians can improve HIV/HCV screening increasing diagnoses and contributing to disease elimination.